DIGITALISASI DALAM PEMERINTAHAN: LANGKAH STRATEGIS PASCA PANDEMI COVID-19 - Ramadhan, Zulfikar (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The COVID-19 pandemic has exposed weaknesses in government systems around the world, driving the need for rapid and effective transformation. Digitalization in government has emerged as one of the most significant strategic steps to face post-pandemic challenges. This research aims to explore the role of digitalization in improving operational efficiency, transparency and quality of public services. Through analysis of case studies from various countries, this article identifies the main benefits of adopting digital technologies, including faster response to emergency situations, more effective monitoring and reporting, and better provision of health and social services. However, digitalization also faces various challenges, such as infrastructure limitations, cyber security, resistance to change, and policy obstacles. This article offers strategic recommendations to overcome these challenges, including developing digital infrastructure, increasing human resource capacity, updating policies, and improving cybersecurity. The method used in this research is the normative juridical legal research method. With commitment and cooperation from various parties, digitalization in government can be the key to building a more resilient and responsive government system in the future